Influence of light and shoot development stage on leaf photosynthesis and carbohydrate status during the adventitious root formation in cuttings of Corylus avellana L. - Tombesi, Sergio; Palliotti, Alberto; Poni, Stefano; Farinelli, Daniela (Frontiers in Plant Science, 2015)
Adventitious root formation in plant cuttings is influenced by many endogenous and environmental factors. Leaf photosynthesis during rooting of leafy cuttings in hard to root species can contribute to supply carbohydrates to the intensive metabolic processes related to adventious root formation. Light intensity during rooting is artificially kept low to decrease potential cutting desiccation, but can be limiting for photosynthetic activity. Furthermore, leafy cuttings collected from different part of the shoot can have a different ability to fuel adventitious root formation in cutting stem. The aim of this work was to determine the role of leaf photosynthesis on adventitious root formation in hazelnut (Corylus avellana L) (a hard-to-root specie) leafy cuttings and to investigate the possible influence of the shoot developmental stage on cutting rooting and survival in the post-rooting phase. Cutting rooting was closely related to carbohydrate content in cutting stems during the rooting process. Cutting carbohydrate status was positively influenced by leaf photosynthesis during rooting. Non saturating light exposure of leafy cuttings can contribute to improve photosynthetic activity of leafy cuttings. Collection of cuttings from different part of the mother shoots influenced rooting percentage and this appear related to the different capability to concentrate soluble sugars in the cutting stem during rooting. Adventitious root formation depend on the carbohydrate accumulation at the base of the cutting. Mother shoot developmental stage and leaf photosynthesis appear pivotal factors for adventitious roots formation.